KORELASI KADAR KALSIUM DAN MASSA OTOT PADA PASIEN PENYAKIT GINJAL KRONIK YANG MENJALANI HEMODIALISIS RUTIN - Triska Dianti Wahyuningrum; Mohammad Rudiansyah; FX Hendriyono (Homeostasis, 2019)
Abstract: Chronic kidney disease (CKD) is the 18th cause of death in the world in 2010. The decline in Glomerular Filtration Rate (GFR) in CKD patients causes hyperphosphatemia which can reduce blood calcium levels. Calcium is an important component in increasing the formation, homeostasis and regeneration of skeletal muscles so calcium can prevent muscle wasting. This study aims to determine the correlation between calcium and muscle mass in CKD patients undergoing routine hemodialysis. The study used an analytic observational design with a cross-sectional approach. This study involved 30 male CKD patients with range of age between 25-59 years old who performed hemodialysis twice a week for at least 3 months in a Hemodialysis Installation at Ulin Hospital Banjarmasin. Subjects were taken by purposive sampling method. The results obtained a median calcium level of 9.4 (8.0 -15.3) mg / dL and an average muscle mass of 34.31 ± 4.389%. From the results of the Spearman Somers'd Gamma correlation test, p = 0.301 which means there is no correlation. There is no correlation between calcium levels and muscle mass in CKD patients undergoing routine hemodialysis. Keywords:Chronic kidney disease, calcium, muscle mass, hemodialysis Abstrak:.Penyakit ginjal kronik (PGK) menjadi penyebab kematian peringkat ke-18 dunia tahun 2010. Penurunan Laju Filtrasi Glomerulus (LFG) pada pasien PGK menyebabkan hiperfosfatemia yang dapat menurunkan kadar kalsium darah. Kalsium merupakan komponen penting dalam peningkatan pembentukan, homeostasis dan regenerasi otot skeletal sehingga kalsium dapat mencegah pengecilan otot. Penelitian ini bertujuan untuk mengetahui korelasi kadar kalsium dan massa otot pada pasien PGK yang menjalani hemodialisis rutin. Penelitian menggunakan rancangan observational analitik dengan pendekatan cross-sectional. Penelitian melibatkan 30 pasien PGK berjenis kelamin laki-laki berusia 25-59 tahun yang melakukan hemodialisis 2 kali seminggu minimal selama 3 bulan di Instalasi Hemodialisis RSUD Ulin Banjarmasin. Subyek diambil dengan metode purposive sampling. Hasilnya didapatkan median kadar kalsium 9,4(8,0 -15,3) mg/dL dan rata-rata massa otot 34,31±4,389%. Dari hasil uji korelasi Spearman Somers’d Gamma didapatkan p=0,301 yang berarti tidak terdapat korelasi. Tidak terdapat korelasi antara kadar kalsium dan massa otot pada pasien PGK yang menjalani hemodialisis rutin. Kata-katakunci: Penyakit ginjal kronik, kalsium, massa otot, hemodialisis